Association between VANGL1 Gene Polymorphisms and Neural Tube Defects - Cai, Chunquan; Shi, Ouyan; Wang, Baiqi; Chang, Baoxing; Yang, Rui; Wang, Yinsong; Wang, Fang; Shen, Changhong (Neuropediatrics, 2014)
Neural tube defects (NTDs) are common, severe congenital malformations. The association between single nucleotide polymorphisms of the VANGL1 gene and NTDs in a Han population of Northern China was principally studied. Missense single nucleotide polymorphisms (rs4839469 c.346G > A p.Ala116Thr and rs34059106 c.1040A > C p.Glu347Ala) of the VANGL1 gene were analyzed by polymerase chain reaction (PCR) and sequencing methods in 135 NTD cases and 135 normal controls. Genotype and allele frequency distribution was calculated, and the spatial structure of the protein was predicted. The results showed that the VANGL1 gene sequence at the rs4839469 locus exhibited Ala116Thr and Ala116Pro polymorphisms, and allele and genotype distributions were significantly different (p = 0.036 and 0.010) between the case and control group. Genotype GC was newly discovered, and its odds ratio value versus GG genotype was 10.241; the α helix fragment of the Ala116Pro mutant was significantly shortened compared with wild type. The rs34059106 site showed alleles of A and did not display C alleles in the two groups. Therefore, the rs4839469 allele of VANGL1 was obviously associated with NTDs. And genotype GC increased the risk of NTDs, changes in the three-dimensional protein structure may have impacted its biological functions, and the rs34059106 polymorphism had no significant correlation with NTDs.
Keywords: neural tube defects; VANGL1; gene polymorphisms